Mengembangkan Kepercayaan Diri Melalui Teknik Role Playing - Konadi, Husrin; Rambe, Syarifah Ainy (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2022)
Early age is a golden age for every individual. Early age is the right time to develop all the potential that exists in the individual. Self-confidence is very important for every individual. Confidence should be cultivated to be developed starting from childhood. Self-confidence is a very good provision for the future for early childhood. Self-confidence is the ability of an individual to express his opinion. Role playing is one of the techniques in counseling that is considered capable of developing individual self-confidence. The purpose of this study was to develop students' self-confidence by using role playing techniques. The research subjects in this study were Kindergarten-A children at Asyiyah Kindergarten, totaling 5 people. The results of this study In the fourth categorys almost the same as the third category. On the first day, four students were still in the undeveloped category and one student in the starting category was developing. This can be seen from the number of students who are reluctant to retell their experiences. But on the second day the students in the category began to develop. On the third day, students have developed as expected. And on the fifth day, the students have achieved very good development.